2013
DOI: 10.1021/ic302484x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization and Physical Properties of the New Transition Metal Oxyselenide La2O2ZnSe2

Abstract: The quaternary transition metal oxyselenide La(2)O(2)ZnSe(2) has been shown to adopt a ZrCuSiAs-related structure with Zn(2+) cations in a new ordered arrangement within the [ZnSe(2)](2-) layers. This cation-ordered structure can be derived and described using the symmetry-adapted distortion mode approach. La(2)O(2)ZnSe(2) is an direct gap semiconductor with an experimental optical band gap of 3.4(2) eV, consistent with electronic structure calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 26 publications
3
36
0
Order By: Relevance
“…It contains both edge-sharing and corner-sharing ZnSe 4 tetrahedra, leading to alternating "checkerboard-like" and "stripe-like" regions along the a axis. This is similar to the La 2 O 2 ZnSe 2 structure, 15 14 where all cations order in a checkerboard arrangement (1C-0E) of corner-sharing tetrahedra. While Zn ordering is the main driver for the symmetry lowering, there are significant accompanying structural distortions, mainly in the Zn-Se tetrahedra shown in Figure 12 and Figure 13.…”
Section: Structure Refinement and Descriptionsupporting
confidence: 61%
“…It contains both edge-sharing and corner-sharing ZnSe 4 tetrahedra, leading to alternating "checkerboard-like" and "stripe-like" regions along the a axis. This is similar to the La 2 O 2 ZnSe 2 structure, 15 14 where all cations order in a checkerboard arrangement (1C-0E) of corner-sharing tetrahedra. While Zn ordering is the main driver for the symmetry lowering, there are significant accompanying structural distortions, mainly in the Zn-Se tetrahedra shown in Figure 12 and Figure 13.…”
Section: Structure Refinement and Descriptionsupporting
confidence: 61%
“…The approach of directly refining the contributions of the different magnetic basis vectors is similar to that originally developed in SARAh [37]. Mode inclusion analysis [25,38] (see Supplemental Material [33] for more details) indicated no change in the Fe moment arrangement on cooling. A good fit could, however, be obtained with an ordered moment on Ce sites.…”
Section: Resultsmentioning
confidence: 99%
“…The ISODISTORT software [34] was used to consider possible distortions and the "mode inclusion method" [42,43] was employed, using the highest resolution backscattered (169 • ) NPD data, to determine which distortions gave the greatest improvement in fit. This analysis indicated that in-plane antipolar displacements (M + 5 ) and in-plane axis octahedral tilts a − a − c 0 (X − 3 ) gave significant improvements in fit, together lowering the symmetry to P nab.…”
Section: B Neutron Powder Diffractionmentioning
confidence: 99%